Determinants of LV mass in athletes: the impact of sport, constitutional traits and cardiovascular risk factors - Pelliccia, A.; Borrazzo, C.; Maestrini, V.; D`Ascenzi, F.; Caselli, S.; Lemme, E.; Squeo, M. R.; Di Giacinto, B. (European Journal of Applied Physiology, 2023)
Background Whether cardiovascular (CV) risk factors might impact Left Ventricular (LV) mass in athletes is unknown.